Modes, genres, and imaginary time component. A proposal for a interpretation - Martín Jiménez, Alfonso (Tropelías: Review of Literary Theory and Comparative Literature, 1993)
The three modes of representation (lyrical, dramatic, and narrative) are parallel to the three possible ways in which man can express his own anthropological self-consciousness and his perception of the world (his otherness). The lyrical mode is suited to the representation of the subject's intimate self, the dramatic mode corresponds to the consciousness of otherness, and the narrative mode provides a synthesis of the other two modes. In addition, the author's choice of a certain mode determines the particular way in which the imaginary component of the work interacts with its material structures. Every type of text (lyrical, dramatic, and narrative) provides a range of specific possibilities of the representation of the imaginary impulses in a temporal and spatial framework. Therefore, the mode of representation decisively conditions the imaginary constitution of the work.
Keywords: Literary genres; anthropology